The Effect of Internet and Library Utilization on Accounting Learning Achievements of Accounting Majors at Vocational School - Lutfiyanah, Lutfiyanah; Purnamasari, Sulfi (International Journal of Economics Education Research (IJEER), 2022)
In this study, the researcher wanted to know the effect of using the internet and libraries on the accounting learning achievement of students majoring in accounting at the SMK Kesatuan for the 2020/2021 academic year. The population in this study were all students majoring in accounting at the SMK Kesatuan both in class X, XI and class XII majoring in Accounting for the academic year 2020/2021 totaling 97. The sample to be tested in this study was 78, consisting of 25 students in class X, 29 students of class XI and 24 students of class XII using random subject sampling technique using the Slovin formula. This study uses quantitative methods and data collection used consists of observation, documentation and questionnaires. The data analysis used was descriptive analysis and inferential statistical analysis using validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis and multiple linear regression analysis. The results of the study indicate that the variable contribution of internet use and library utilization to accounting learning achievement of students majoring in accounting is 13.9%, while the remaining 86.1% is influenced by other factors not examined. in this research. The significance value of the anova output is 0.004 < 0.05 (significant level) so that H0(3) is rejected and H3 is accepted. So it can be said that the simultaneous use of the internet and the use of libraries on the learning achievement of accounting students at the SMK Kesatuan Jakarta Barat for the 2020/2021 academic year.